Differences of bleedings after percutaneous coronary intervention using femoral closure and radial compression devices - Kim, Seung‑Hyun; Behnes, Michael; Baron, Sebastian; Shchetynska-Marinova, Tetyana; Tekinsoy, Melike; Mashayekhi, Kambis; Hoffmann, Ursula; Borggrefe, Martin; Akın, Ibrahim (Medicine, 2019)
Bleedings represent most relevant complications being correlated with significant rates of adverse clinical outcomes in patients undergoing percutaneous coronary intervention (PCI). To reduce bleeding and improve prognosis various types of vascular closure devices (VCD) are frequently applie